1986
DOI: 10.1038/321079a0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro osteoclast generation from different bone marrow fractions, including a highly enriched haematopoietic stem cell population

Abstract: It is well established that the osteoclast is formed by fusion of post-mitotic, mononuclear precursors derived from circulating progenitor cells. However, the precise haematopoietic origin of the osteoclast is unknown. We have investigated this here by fractionating mouse bone marrow and isolating haematopoietic stem cells using a three-step method combining equilibrium density centrifugation and two fluorescence-activated cell sortings (FACS), and have tested the ability of each bone marrow fraction, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
103
1
2

Year Published

1988
1988
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(108 citation statements)
references
References 11 publications
2
103
1
2
Order By: Relevance
“…[2][3][4][5][6]34 Regardless of the precise origin of OCL progenitors, it is clear that any disruption of hematopoiesis can profoundly affect OCL numbers. In the current study we found that an IMiD of thalidomide (CC-4047) inhibits the generation and differentiation of OCLs by down-regulation of PU.1, resulting in a shift of lineage commitment of hematopoietic progenitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6]34 Regardless of the precise origin of OCL progenitors, it is clear that any disruption of hematopoiesis can profoundly affect OCL numbers. In the current study we found that an IMiD of thalidomide (CC-4047) inhibits the generation and differentiation of OCLs by down-regulation of PU.1, resulting in a shift of lineage commitment of hematopoietic progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…OCLs are multinucleated cells that derive from monocyte/macrophage lineage cells. [2][3][4][5][6] How commitment to a given lineage occurs among macrophages, OCLs, and dendritic cells has not been fully elucidated, but complex signaling mechanisms are known to control OCL differentiation. 7 These signals include cytokines such as macrophage colony-stimulating factor (CSF-M), granulocytemacrophage colony-stimulating factor (CSF-GM), and interleukin-3, 8 which are macrophage-inducing cytokines, and the receptor activator of NF-B ligand (RANKL), which is a critical factor for late stages of OCL development.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of these receptors in bone cells does not vary by gender, as similar levels of ER and AR have been found in bone cells from males and females (Benz et al, 1991a,b;Braidman et al, 2000). However, in spite of the demonstration of receptors, convincing evidence that estrogens or androgens modulate the biosynthetic activity of osteoblasts and osteoclasts in a manner that can explain the welldocumented skeletal effects of estrogen loss in vivo remained elusive until the critical role of the bone marrow in bone remodeling was appreciated about a decade ago (Scheven et al, 1986;Kurihara et al, 1989).…”
Section: Effects Of Sex Steroids On Osteoclastogenesismentioning
confidence: 99%
“…Early studies had demonstrated that OCPs originate from the haematopoietic stem cells (Sheven et al, 1986;Hagenaars et al, 1989;Hattersley & Chambers, 1989;Kurihara et al, 1989;Matayoshi et al, 1996) and circulate in PB (Walker, 1973(Walker, , 1975Kahn & Simmons, 1975;Coccia et al, 1980;Faust et al, 1999;. However, whether OCPs possess surface characteristics that distinguish them from other PBMCs (in particular monocytes) is not known.…”
mentioning
confidence: 99%